The implementation of cooperative learning type team assisted individualisation for teaching 3D geometry - Lia Budi Tristanti; Wiwin Sri Hidayati (Journal of Education and Learning (EduLearn), 2020)
This study aimed to investigate the effectiveness of a cooperative learning type TAI for teaching 3D geometry and to see whether or not the outcome of cooperative learning type TAI was found better for teaching 3D geometry rather than conventional learning model.  This study was a experiment with pretest posttest only control design. The sample are 70 students on the first grade of MA Ismailiyah, Jombang. The sample randomly divided into two classes, that is experimental class and control class. The experimental class used the cooperative learning type TAI, while the control class used the conventional learning model.The instruments consisted of observation sheet for students’ activities, observation sheet for students’ cooperative skills, questionnaire of students’ responses and test sheet of learning outcome. The findings showed that the implimentation of a cooperative learning type TAI for teaching 3D geometry is effective and the outcomes of the students taught 3D geometry using TAI were found better than ones taught using a conventional learning model.